2001
DOI: 10.1128/jcm.39.8.2971-2974.2001
|View full text |Cite
|
Sign up to set email alerts
|

Candida Species Exhibit Differential In Vitro Hemolytic Activities

Abstract: A total of 80 Candida isolates representing 14 species were examined for their respective responses to an in vitro hemolytic test. A modification of a previously described plate assay system where the yeasts are incubated on glucose (3%)-enriched sheep blood agar in a carbon dioxide (5%)-rich environment for 48 h was used to evaluate the hemolytic activity. A group of eight Candida species which included Candida albicans (15 isolates), C. dubliniensis (2), C. kefyr (2), C. krusei (4), C. zeylanoides (1), C. gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
204
3
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(240 citation statements)
references
References 16 publications
8
204
3
16
Order By: Relevance
“…This darkened area turns bluish green and then clears over 24 to 48 h (Van Emon et al, 2003;Vesper et al, 2001). (This is similar to the slow reaction described by Luo et al [2001] for the Candida hemolysins.) C. BACTERIAL HEMOLYSINS Bacterial hemolysins are a fairly heterogenous group of proteins, but they have been classified in many cases into three ''families'' of toxins.…”
Section: Filamentous Fungisupporting
confidence: 56%
See 1 more Smart Citation
“…This darkened area turns bluish green and then clears over 24 to 48 h (Van Emon et al, 2003;Vesper et al, 2001). (This is similar to the slow reaction described by Luo et al [2001] for the Candida hemolysins.) C. BACTERIAL HEMOLYSINS Bacterial hemolysins are a fairly heterogenous group of proteins, but they have been classified in many cases into three ''families'' of toxins.…”
Section: Filamentous Fungisupporting
confidence: 56%
“…More recently, C. albicans was shown to produce a -hemolytic agent, but it was not characterized (Manns et al, 1994). In a more comprehensive study, Luo et al (2001) tested the hemolytic activity of 14 Candida species. C. albicans, C. dubliensis, C. kefyr, C. krusei, C. zeylanoides, C. glabrata, C. tropicalis, and C. lusitaniae all produced alpha hemolysis at 24 h, which led to beta hemolysis at 48 h. Candida famata, C. guilliermondii, C. rugosa, and C. utilis produced only alpha hemolysis, and C. parapsilosis and C. pelliculosa demonstrated no hemolytic activity.…”
Section: A Hemolysins Produced By Macro-fungimentioning
confidence: 99%
“…The haemolytic activity was determined by a blood agar plate assay method (Luo et al, 2001). The medium was prepared by adding 7 ml fresh sheep blood to 100 ml SDA supplemented with 3 % glucose, giving a final concentration of 7 %.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…In the particular case of haemolysins, Luo et al (2001) showed that glucose added to aerobic blood agar can increase the detection of haemolytic activity in some strains. Shuster et al (2004) described the phenomenon of 'microbial alcohol-conferred haemolysis' and showed that ethanol is readily oxidized to acetaldehyde with a strong haemolytic behaviour.…”
Section: Resultsmentioning
confidence: 99%